Perceived Benefit of Condom Use Domination on the Perceived Benefit of Sexually Transmitted Infection Screening on Queer in Yogyakarta - Fika Lilik Indrawati; Argyo Demartoto; Ari Natalia Probandari (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: The negative stigma is inherent in transvestites because it is referred to as one of the sources of the spread of STIs and HIV/ AIDS viruse. In their position as a sex worker who was considered very low and lack of knowledge about reproductive health, the transvestites were infected with STIs and the HIV virus from their sexual partners. This happened because of a lack of information about reproductive health and access to health services for queer. This study aimed to analyze perceived benefit of condom use domination on the perceived benefit of sexually transmitted infection screening on queer.Subjects and Method: This was a qualitative study with phenomenological approach. Seven representative informants were selected by purposive sampling. The data were collected by in-depth interview and focus group discussion. The number of informants at the focus group discussion was eight people.Results: Most of the informants believed that they were able to avoid or recover from STIs by using safety, namely condoms. They are more convinced that by applying condoms to their partners, it will be more useful as prevention of STIs compared to STI screening, on the grounds that practical condoms are easy to carry and do not hurt when having sexual intercourse.Conclusion: All transvestites believe that STI screening can be beneficial to their health, but the reality in their behavior is that they believe in condoms as a means of preventing STIs.Keywords: condom, STI screening service, queerCorrespondence: